2010
DOI: 10.5851/kosfa.2010.30.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Reconstituted Milk Made from Freeze-dried Milk Powder or Spray-dried Milk Powder

Abstract: This study was designed to compare the physicochemical and nutritional properties between reconstituted milk samples made from freeze-dried milk powder (FDMP) and spray-dried milk powder (SDMP). Reconstituted milk (87%, wb) was made by combining FDMP or SDMP with water. In the color analysis, the L*, a* and b* values of the reconstituted milk samples made from both powders were not significantly different from the control. The thiobarbituric acid values and shortchain free fatty acid concentrations were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…However, it did not exceed 0.2 until 4 d storage except 3% supplementation of PPSEM in milk which exceeded 0.2 from 0 d. However, 0.5 and 1.0% PPSEM-supplemented milks maintained the lower value of 0.2 up to 16 d. These results are in accordance with the findings of Tuohy et al (1981) and Ipsen and Hansen (1988) which stated that increasing storage time favored more oxidation and increased the TBARS value in whole milk powder. Also, freeze-dried milk powder and spray-dried milk powder were observed where TBA values increased with the increasing storage during 20 d ( Kim et al, 2010 ). Further, Ahn et al (2010) reported that TBA-values of encapsulated I. obliquus extract-added milk samples increased during storage.…”
Section: Resultsmentioning
confidence: 99%
“…However, it did not exceed 0.2 until 4 d storage except 3% supplementation of PPSEM in milk which exceeded 0.2 from 0 d. However, 0.5 and 1.0% PPSEM-supplemented milks maintained the lower value of 0.2 up to 16 d. These results are in accordance with the findings of Tuohy et al (1981) and Ipsen and Hansen (1988) which stated that increasing storage time favored more oxidation and increased the TBARS value in whole milk powder. Also, freeze-dried milk powder and spray-dried milk powder were observed where TBA values increased with the increasing storage during 20 d ( Kim et al, 2010 ). Further, Ahn et al (2010) reported that TBA-values of encapsulated I. obliquus extract-added milk samples increased during storage.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with the observations of Kim et al . (), who found better hydration properties for a freeze‐dried sample of milk compared to a spray‐dried sample. In general, the better hydration properties of freeze‐dried emulsions compared to spray‐dried samples can be attributed to a higher porosity of the solid wall (Sims, ; Barbosa‐Cánovas et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Undesirable changes and/or loss of some components such of proteins, oil, vitamins and others may occur due to the high temperatures applied in the spray‐drying process (Kim et al ., ). An alternative dehydration method for heat sensitive products is freeze‐drying, whose use is not extended in the food industry owing to economic reasons.…”
Section: Introductionmentioning
confidence: 97%
“…Kim ve ark. [59] yaptıkları çalışmada püskürtmeli kurutma ve dondurarak kurutma ile elde edilen tam yağlı süt tozlarının rekonstitüe halleri ile sütü analiz etmişler ve serbest yağ asidi miktarlarını belirlemişler. Analizde sadece kısa zincirli serbest yağ asitleri belirlenmiş ve püskürtmeli kurutma ile üretilmiş tozda serbest yağ asidi miktarının arttığı saptanmıştır [59].…”
Section: Yağlı Toz üRünlerde Serbest Yağ Asidi Bileşimiunclassified
“…[59] yaptıkları çalışmada püskürtmeli kurutma ve dondurarak kurutma ile elde edilen tam yağlı süt tozlarının rekonstitüe halleri ile sütü analiz etmişler ve serbest yağ asidi miktarlarını belirlemişler. Analizde sadece kısa zincirli serbest yağ asitleri belirlenmiş ve püskürtmeli kurutma ile üretilmiş tozda serbest yağ asidi miktarının arttığı saptanmıştır [59]. Püskürtmeli kurutma işlem koşullarının etkisi üzerine literatürde kesin veriler sunan bir çalışma olmamakla beraber, giriş sıcaklığının ve/veya çıkış sıcaklığının arttırılması ile uçucu bileşenlerin miktarının arttığına dair veriler vardır [60].…”
Section: Yağlı Toz üRünlerde Serbest Yağ Asidi Bileşimiunclassified